Proposed Marketing Communication Strategy to Increase Buyer’s Decision to Buy House (Case Study: PT. Sedulur Guyub Rukun) - Radityo Chrisna Adi; Sonny Rustiadi (Institut Teknologi Sepuluh Nopember, 2019)
PT. Sedulur Guyub Rukun is a property developer with the main business as a housing developer with premium-class products in Jombang, East Java. the house residence name is Jombang Citra Raya. In recent year, the company faced the decreases in sales as a business problem and this research examine the business issue and solve the issue with the proposed business strategy. The research uses several analytic tools such as internal analysis uses STP, Marketing Mix analysis and In-depth interview, for external analysis uses Five Porter’s forces, Competitor analysis questionnaire with multiple linear regression model. The analytic tools are used to formulate business solution that able to increase customers purchasing decision to buy a house and increase the brand awareness of the company by using a marketing communication strategy. From 100 respondents are used as the sample for the questionnaire, the result finds the most significant factor to influence the buyer’s decision is Products and the least factors are Prices. This research result becomes the reference to build Integrated Marketing Communication (IMC) that consists of advertising, publicity and sales promotion as marketing communication media for the IMC strategy. To implement it, the schedule plan and budget allocation for IMC is proposed.